Method for improving poor final sealing of semi-solid battery
By using two liquid injection and two pre-charge methods in the production process of semi-solid battery, the problem of final sealing caused by the overflow of electrolyte during high-temperature curing is solved, and the safety and performance of the battery are improved.
Patent Information
- Application Number
- CN202411656568.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-14
AI Technical Summary
During the high-temperature curing process of existing semi-solid batteries, the free electrolyte is affected by pressure, and some electrolyte spills to the final sealing position, forming gel electrolyte, resulting in poor final sealing and increasing safety risks.
The process flow of two injections and two pre-fillings is adopted: the first injection is part of the organic electrolyte and all monomers, and the second injection is the remaining organic electrolyte and all initiators, and it is passed through two infiltrations and high temperatures. Curing to form a uniform electrolyte structure and a good SEI film.
It effectively reduces the presence of gel electrolyte at the final sealing position, improves the safety and performance of the battery, ensures the good state of the final seal, and reduces the risk of false sealing.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery preparation, and in particular to a method for improving final sealing defects of a semi-solid (soft-pack) battery. Background Art
[0002] Organic liquid electrolyte batteries inevitably produce side reactions during the charging and discharging process. When using a high-nickel positive electrode + silicon-based negative electrode system, the 350Wh / kg of liquid batteries may be close to the limit energy density of liquid lithium batteries, and no further breakthroughs can be achieved. Solid-state batteries can adapt to higher capacity materials, and the energy density can reach 500Wh / Kg. The iteration of chemical systems is the core of the development of the power battery industry, and solid-state batteries can be said to be the next generation of deterministic direction. Solid-state batteries cover a certain broad concept, including semi-solid, solid-state and all-solid-state batteries. Strictly speaking, there is no liquid phase inside solid-state batteries, but in relatively broad situations, batteries with solid electrolytes can also be called "solid-state batteries" to a certain extent. At this stage, solid-state batteries are mainly distinguished according to the type of electrolyte, mainly polymer solid-state batteries, oxide solid-state batteries, and sulfide solid-state batteries. The current semi-solid-state battery is between all-solid-state and liquid batteries. As a transition before all-solid-state batteries, initiators and monomers are added to liquid batteries to achieve gelation of electrolytes, thereby improving the safety performance of batteries. With polymer as the skeleton network of electrolyte, lithium salt and electrolyte with plasticizing effect are distributed in the polymer matrix as the main lithium conductive medium, and a gel electrolyte will be obtained. However, the formation of gel electrolyte will pose a great challenge to the production process of the battery. With the current mainstream production process route, the battery cell is cured at high temperature after infiltration. Since the high temperature curing is carried out under high temperature and high pressure, the free electrolyte in the core package is affected by the pressure during pressurization, and part of the electrolyte will overflow to the final sealing position. After the high temperature curing is completed, a large amount of gel electrolyte will be formed at the final sealing position, resulting in poor final sealing. When the package is virtual sealed, moisture, oxygen, etc. in the air will enter the battery cell. There are currently two main methods to solve the problem of poor final sealing. One is to remove the gel electrolyte at the final sealing position through a scraping device after high temperature curing, as disclosed in the publication number CN220942044U, but this method cannot fundamentally reduce the presence of gel electrolyte at the final sealing position, and cannot guarantee 100% yield. The second is as disclosed in CN117254122A, a protective film is affixed to the final sealing edge of the shell for final sealing; in the final sealing process of the soft-pack battery, the soft-pack battery is placed in a vacuum environment, the airbag bag is cut off, and the protective film at the final sealing edge is torn off to final seal the final sealing edge. However, this method also requires manual secondary operation and cannot fundamentally reduce the generation of gel electrolyte at the final seal. Therefore, it is urgent to explore a process and preparation method to fundamentally reduce the presence of gel electrolyte at the final seal, so as to reduce the risk of false sealing of the final seal and improve the safety of the battery. Summary of the invention
[0003] After the semi-solid battery cell is filled with liquid and soaked at room temperature, it is cured at high temperature. Since the high-temperature curing is carried out under high temperature and high pressure, the free electrolyte in the core package is affected by the pressure, and part of the electrolyte will overflow to the final sealing position. After the high-temperature curing is completed, a large amount of gel electrolyte will be formed at the final sealing position, which will eventually cause poor gel. At present, the gel electrolyte at the seal is manually erased and a protective film is attached to the final sealing edge, and the protective film is torn off before packaging. Both methods require manual intervention, which is time-consuming and labor-intensive, and cannot be mass-produced, and cannot fundamentally solve the problem of gel electrolyte generated at the final sealing position. Therefore, it is urgent to develop a process to fundamentally solve the problem of gel electrolyte generated at the final sealing position, reduce the safety risks of semi-solid batteries, and improve the safety of semi-solid batteries.
[0004] A method for improving the poor final sealing of a semi-solid battery comprises: (1) injecting a battery cell once, wherein the first injection is a partial organic electrolyte and all monomers; (2) after the first injection battery cell is packaged, an infiltration and a first pre-charging are performed, so that the electrolyte fully infiltrates the pole piece, the monomers are fully dispersed inside the pole piece, a uniform structure is formed, and a partial SEI film is formed; (3) a second injection is performed, wherein the second injection is the remaining organic electrolyte and all initiators; (4) after the second injection battery cell is packaged, a second infiltration is performed, and after completion, the battery cell is subjected to high-temperature curing; (5) the cured battery cell is subjected to a first degassing, and then a second pre-charging is performed, after the pre-charging generates gas, a second degassing is performed, and then a constant volume is performed, and after the constant volume is completed, a final sealing is performed to fully form an SEI film.
[0005] In the method for improving the poor final sealing of semi-solid batteries, further, the first injection amount of the organic electrolyte is 60-90wt% of the total injection amount; and the second injection amount is the remaining electrolyte.
[0006] Furthermore, the proportions of the organic electrolyte, the monomer, and the initiator are 90wt%-98wt%, 1wt%-9wt%, and 0.02wt%-5wt%, respectively.
[0007] Further, the organic electrolyte is composed of a lithium salt and an organic solvent; wherein the lithium salt includes: lithium tetrafluoroborate (LiBF4), lithium hexafluoroarsenate (LiAsF6), lithium hexafluorophosphate (LiPF6), lithium bis(oxalate borate) (LiBOB), lithium difluorooxalate borate (LiDFOB), lithium bis(fluorosulfonyl imide) salt (LiFSI), lithium bis(trifluoromethylsulfonyl imide) (LiTFSI), lithium trifluoromethanesulfonate (LiCF3SO3), lithium tetrafluoroborate (LiBF4), lithium difluorooxalate borate (LiODFB), lithium difluorobis(oxalate phosphate) (LiDFBP) in one or more. Further, the organic solvent includes: ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, fluorinated ethylene carbonate, dipropyl carbonate, dimethyl sulfoxide dimethoxyethane, N-methyl-2-pyrrolidone, γ-butyrolactone, polyethylene glycol dimethyl ether in one or more.
[0008] Further, the monomer includes: 2-bromoethyl acrylate, hydroxypropyl acrylate, isostearyl acrylate, isobutyl methacrylate, 4-hydroxybutyl acrylate, tributyltin acrylate, propane-1,3-diyl diacrylate, trimethylolpropane triacrylate, 4-ethylbenzene acrylate, hydroxyethyl acrylate, hydroxypentabromophenyl methacrylate, pentabromophenyl acrylate, 6-bromo-1-hexyl acrylate, 2-bromoethyl acrylate, 2-chloroethyl methacrylate, 11-phosphonic acid undecyl acrylate, tributyltin acrylate, 2-(perfluorobutyl)ethyl acrylate.
[0009] Further, the initiator includes: one or more of azobisisobutyronitrile, azobisisoheptanenitrile, azobisdimethylvaleronitrile, cumene hydroperoxide, tert-butyl hydroperoxide, p-menane hydroperoxide, potassium persulfate, ammonium persulfate, lauroyl peroxide, dibenzoyl peroxide, and dodecanoyl peroxide.
[0010] Furthermore, the time for the first and second infiltration is 12-48 hours to ensure sufficient infiltration of the electrolyte.
[0011] Furthermore, the high temperature curing conditions are: temperature 40-90°C, pressure 300-600kgf, time 2-6h.
[0012] The same steps are used for the primary pre-charging and the secondary pre-charging: (for example, at a temperature of 30°C and a pressure of 1500Kgf); the constant current charging is specifically to use a constant current of 0.01C-0.3C to charge the vacuum-sealed battery cell to 3.8V; for example: ① constant current charging, 0.05C, charging to 3.8V; ② constant current charging, 0.1C, charging to 3.8V; ③ constant current charging, 0.2C, charging to 3.8V; ④ standing.
[0013] In the above method of the present invention, the first infiltration is 12-48 hours to ensure that the electrolyte is fully infiltrated; the first pre-filling is performed after the first injection to disperse the organic electrolyte and the monomer to ensure that the electrolyte is fully infiltrated and the monomer is fully dispersed inside each electrode; the second infiltration is 12-48 hours to ensure that the electrolyte prepolymer is fully infiltrated; the second pre-filling is performed to ensure that the SEI film is fully formed; the second injection can avoid the generation of a large amount of free electrolyte.
[0014] Through the above method, the electrolyte can fully infiltrate the electrode, and there is less free electrolyte. Through two injections and two pre-chargings, the electrode can fully absorb the electrolyte, greatly improving the wetting effect. The two pre-chargings can also improve the initial effect and ensure good performance.
[0015] Beneficial effects:
[0016] The method for improving the poor final sealing of semi-solid batteries of the present invention requires two injections and two pre-charges. The monomer needs to be introduced in the first injection. The monomer is introduced first, and the first pre-charge is performed to ensure the subsequent dispersion effect. The initiator needs to be introduced in the second injection to ensure that the electrolyte is fully infiltrated during high-temperature curing, reduce the generation of free electrolyte, and the prepolymer is evenly dispersed. The two pre-charges can ensure that the electrolyte, monomer, and initiator can fully infiltrate the inside of the pole piece and form a good SEI film, improve the first effect of the battery, and make the battery have good performance.
[0017] The present invention has been described in detail above, but the above embodiments are only illustrative in nature and are not intended to limit the present invention. In addition, this article is not limited by any theory described in the above prior art or invention content or the following examples. DETAILED DESCRIPTION
[0018] The present invention is further described below in conjunction with examples. It should be noted that the following examples are provided for illustrative purposes only and do not constitute a limitation on the scope of protection claimed for the present invention.
[0019] Unless otherwise specified, the raw materials, reagents, methods, etc. used in the examples are conventional raw materials, reagents, methods in the art.
[0020] The final seal defect detection method is as follows: ① Use a blade to scrape the seal position. If there is no opening, it means the seal is good. ② Visually check whether there is an opening at the seal position. If there is an opening, it means the seal is bad. Interface inspection method: Disassemble with full power and observe the interface.
[0021] Comparative Example 1 (one-time injection, poor final sealing)
[0022] (1) preparing a ternary positive electrode sheet by slurrying, coating, rolling, slitting, die-cutting and other processes, preparing a silicon-based graphite negative electrode sheet by slurrying, coating, rolling, slitting, die-cutting and other processes, and trial-producing a dry battery cell by laminating, welding, heat-sealing and other processes the prepared positive and negative electrode sheets and separators;
[0023] (2) After weighing and mixing an organic electrolyte, a monomer, and an initiator in a ratio of 94.9 wt%, 3.8 wt%, and 1.7 wt%, the organic solvent and the monomer are stirred for 30 min to mix evenly; then the initiator is added and stirred for 30 min to finally form an electrolyte mixed prepolymer. The total injection amount of a single semi-solid battery cell is controlled at 180 g, i.e., 170.1 g of organic electrolyte (1 M LiPF6 / EC+EMC), 6.848 g of monomer (2-bromoethyl acrylate), and 3.06 g of initiator (azobisisobutyronitrile).
[0024] (3) Inject the electrolyte mixed with the prepolymer into the battery cell at one time for the first packaging. The sealed battery cell is placed in a room temperature static storage for immersion for 24 hours.
[0025] (4) The impregnated battery cell is subjected to high temperature curing at a temperature of 60°C, a pressure of 400 kgf, and a time of 6 hours.
[0026] (5) After curing, the battery cell is degassed for the first time and then pre-charged. After the pre-charge produces gas, it is degassed for the second time and then fixed in volume. After the fixed volume is completed, it is finally sealed.
[0027] Verification results: After high-temperature curing, a large amount of gel exists in the final sealing position, which seriously affects the final sealing effect and causes the problem of virtual sealing and leakage.
[0028] Comparative Example 2 (Secondary injection, first injection of 55% electrolyte, second injection of monomer + initiator + remaining electrolyte, one pre-charge, lithium precipitation)
[0029] (1) preparing a ternary positive electrode sheet by slurrying, coating, rolling, slitting, die-cutting and other processes, preparing a silicon-based graphite negative electrode sheet by slurrying, coating, rolling, slitting, die-cutting and other processes, and trial-producing a dry battery cell by laminating, welding, heat-sealing and other processes the prepared positive and negative electrode sheets and separators;
[0030] (2) First injection: The total injection volume of a single semi-solid battery cell is controlled at 180 g, and the injection volume is 55% of the total injection volume, that is, 99 g of organic electrolyte (1M LiPF6 / EC+EMC). The first injection only injects part of the organic electrolyte, without injecting monomers and initiators.
[0031] (3) After the electrolyte is injected into the battery cell, the first packaging is performed. The sealed battery cell is placed in a room temperature static storage for immersion for 24 hours.
[0032] (4) Second injection: The remaining 71.1 g of organic electrolyte and 6.848 g of monomer (2-bromoethyl acrylate) were mixed and stirred for 30 min, and then 3.06 g of initiator (azobisisobutyronitrile) was added and stirred for 30 min to mix evenly.
[0033] (5) After the second injection, the battery cell is packaged and placed in a room temperature static warehouse for a second soaking, with a soaking time of 24 hours.
[0034] (6) The impregnated battery cell is subjected to high temperature curing at a temperature of 60°C, a pressure of 400 kgf, and a time of 6 hours.
[0035] (7) After the solidification, the battery cell is degassed for the first time and then pre-charged. After the pre-charge produces gas, it is degassed for the second time and then fixed in volume. After the fixed volume is completed, it is finally sealed.
[0036] Verification results: There is no gel at the final sealing position, but there is lithium deposition at the fully charged disassembly interface. The reason is that the organic electrolyte is injected in advance as a matrix, which causes the monomer and initiator to be unable to be fully dispersed inside the electrode, resulting in lithium deposition.
[0037] Comparative Example 3 (Secondary injection, the first injection of electrolyte + monomer 55%, the second injection of remaining electrolyte + initiator, one pre-filling, incomplete infiltration, and traces of infiltration)
[0038] (1) preparing a ternary positive electrode sheet by slurrying, coating, rolling, slitting, die-cutting and other processes, preparing a silicon-based graphite negative electrode sheet by slurrying, coating, rolling, slitting, die-cutting and other processes, and trial-producing a dry battery cell by laminating, welding, heat-sealing and other processes the prepared positive and negative electrode sheets and separators;
[0039] (2) First injection: The total injection volume of a single semi-solid battery cell is controlled at 180 g, and the injection volume is 55% of the total injection volume, namely, 92.16 g of partial organic electrolyte (1M LiPF6 / EC+EMC) and 6.84 g of all monomers (2-bromoethyl acrylate). The first injection only injects part of the organic electrolyte and monomers, and no initiator is injected.
[0040] (3) After the electrolyte is injected into the battery cell, the first packaging is performed. The sealed battery cell is placed in a room temperature static storage for immersion for 24 hours.
[0041] (4) Second injection: 3.06 g of initiator (azobisisobutyronitrile) was stirred for 30 min to mix well, and then the second injection was performed.
[0042] (5) After the second injection, the battery cell is packaged and placed in a room temperature static warehouse for a second soaking, with a soaking time of 24 hours.
[0043] (6) The impregnated battery cell is subjected to high temperature curing at a temperature of 60°C, a pressure of 400 kgf, and a time of 6 hours.
[0044] (7) After the solidification, the battery cell is degassed for the first time and then pre-charged. After the pre-charge produces gas, it is degassed for the second time and then fixed in volume. After the fixed volume is completed, it is finally sealed.
[0045] Verification results: There is no gel at the final sealing position, and there is no lithium deposition on the fully charged disassembly interface, but there are signs of insufficient wetting. After full charge, there are white spots on the top of the middle layer electrode. This is mainly because the electrolyte cannot fully infiltrate the electrode, resulting in interface abnormalities and a low initial efficiency of about 80%.
[0046] Example 1 (Secondary injection, the first injection is 65% electrolyte + monomer, the second injection is the remaining electrolyte + initiator, two pre-filling, immersion for 24 hours, good interface, excellent performance test, by increasing the number of pre-filling + adjusting the dosage and secondary injection, the electrode interface abnormality and other problems are perfectly solved, and the final sealing sol is good)
[0047] (1) preparing a ternary positive electrode sheet by slurrying, coating, rolling, slitting, die-cutting and other processes, preparing a silicon-based graphite negative electrode sheet by slurrying, coating, rolling, slitting, die-cutting and other processes, and trial-producing a dry battery cell by laminating, welding, heat-sealing and other processes the prepared positive and negative electrode sheets and separators;
[0048] (2) First injection: The total injection volume of a single semi-solid battery cell is controlled at 180 g, and the injection volume is 65% of the total injection volume, namely, 110.16 g of partial organic electrolyte (1M LiPF6 / EC+EMC) and 6.84 g of all monomers (2-bromoethyl acrylate). The first injection only injects part of the organic electrolyte and monomers, and no initiator is injected.
[0049] (3) After the electrolyte is injected into the battery cell, the first packaging is performed. The sealed battery cell is placed in a room temperature static storage for immersion for 24 hours.
[0050] (4) First pre-charge: Pre-charge with a small current to allow the electrolyte to fully infiltrate the electrode, and the monomer to fully disperse inside the electrode to form a uniform structure and a partial SEI film. The first pre-charge is carried out at a temperature of 30°C and a pressure of 1500Kgf, specifically: ① Constant current charging, 0.05C, charging to 3.8V; ② Constant current charging, 0.1C, charging to 3.8V; ③ Constant current charging, 0.2C, charging to 3.8V; ④ Standing.
[0051] (5) Second injection: The remaining organic electrolyte and all the initiator (azobisisobutyronitrile) 3.06 g were stirred for 30 min to mix evenly, and then the second injection was performed.
[0052] (6) After the second injection, the battery cell is packaged and placed in a room temperature static warehouse for a second soaking, with a soaking time of 24 hours.
[0053] (7) The impregnated battery cell is subjected to high temperature curing at a temperature of 60°C, a pressure of 400 kgf, and a time of 6 hours.
[0054] (8) After curing, the battery cell is degassed for the first time, and then pre-charged for the second time. After the pre-charged gas is generated, the battery cell is degassed for the second time, and then the battery cell is fixed to the same volume. After the fixed volume is completed, the battery cell is finally sealed. The secondary pre-charge is carried out at a temperature of 30°C and a pressure of 1500Kgf, specifically: ① constant current charging, 0.05C, charging to 3.8V; ② constant current charging, 0.1C, charging to 3.8V; ③ constant current charging, 0.2C, charging to 3.8V; ④ standing.
[0055] After multiple attempts at the above solutions, the final cell capacity was between 100.5-101.8Ah, IR was between 0.9-0.95mΩ, first efficiency was between 87-89%, and the liquid retention was around 158g. There was no obvious difference or abnormality in the process. The results of the electrical performance test and safety test are as follows:
[0056] ①Electrical performance test:
[0057] The capacity retention rate of 2C charging rate is 70%;
[0058] The 2C discharge capacity retention rate is 96%;
[0059] After 28 days of storage at room temperature, the capacity retention rate is 98% and the capacity recovery rate is 99%;
[0060] After 30 days of high-temperature storage, the capacity retention rate is 95% and the capacity recovery rate is 97.5%.
[0061] ②Safety test:
[0062] Short circuit test - no fire or explosion in a full-charge short circuit test;
[0063] Needle puncture test: 20% SOC needle puncture does not cause fire or explosion;
[0064] Heating test - passed 150℃ hot box without fire or explosion; Extrusion test - passed 50% extrusion test without fire or explosion.
[0065] It can be seen that the present invention improves the first injection volume and the secondary pre-filling and secondary injection, and finally has good interface performance, no abnormalities in the final sealing, and a high first efficiency of about 88%, and no abnormalities in various electrical performance tests and safety tests; this is impossible to achieve with other solutions such as the comparative example.
[0066] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents, without departing from the spirit and essence of the claims of the present invention; and these modifications or replacements are still within the scope defined by the claims of the present invention.
Claims
1. A method for improving the poor final sealing of a semi-solid battery, characterized in that: include: (1) The battery cell is injected with liquid once, and the liquid is injected with part of the organic electrolyte and all the monomers; (2) After the cell with liquid injection is packaged, it is impregnated once and pre-charged for the first time, so that the electrolyte fully impregnates the electrode, the monomers are fully dispersed inside the electrode, a uniform structure is formed, and a part of the SEI film is formed; (3) The second liquid injection is performed, and the second liquid injection is the remaining organic electrolyte and all the initiators; (4) After the cell with liquid injection is packaged, it is impregnated for the second time, and the cell is cured at high temperature after completion; (5) The cured cell is degassed for the first time, and then pre-charged for the second time. After the pre-charge generates gas, it is degassed for the second time, and then fixed volume is performed. After the fixed volume is completed, it is finally sealed to fully form the SEI film.
2. A method for improving the poor final sealing of a semi-solid battery as claimed in claim 1, further characterized in that the first injection amount of the organic electrolyte is 60-90wt% of the total injection amount; and the second injection is the remaining electrolyte.
3. A method for improving the poor final sealing of a semi-solid battery as claimed in claim 1 or 2, further characterized in that the proportions of the organic electrolyte, the monomer, and the initiator are 90wt%-98wt%, 1wt%-9wt%, and 0.02wt%-5wt%, respectively.
4. A method for improving the poor final sealing of a semi-solid battery as claimed in claim 1 or 2, further characterized in that the organic electrolyte consists of a lithium salt and an organic solvent; wherein the lithium salt comprises: One or more of lithium tetrafluoroborate (LiBF4), lithium hexafluoroarsenate (LiAsF6), lithium hexafluorophosphate (LiPF6), lithium bis(oxalatoborate) (LiBOB), lithium difluorooxalatoborate (LiDFOB), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiCF3SO3), lithium tetrafluoroborate (LiBF4), lithium difluorooxalatoborate (LiODFB), and lithium difluorobis(oxalatophosphate) (LiDFBP).
5. A method for improving the final sealing failure of a semi-solid battery as claimed in claim 4, further characterized in that the organic solvent comprises: One or more of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, fluorinated ethylene carbonate, dipropyl carbonate, dimethyl sulfoxide dimethoxyethane, N-methyl-2-pyrrolidone, γ-butyrolactone, and polyethylene glycol dimethyl ether.
6. A method for improving the final sealing failure of a semi-solid battery as claimed in claim 1 or 3, further characterized in that the monomer comprises: One or more of 2-bromoethyl acrylate, hydroxypropyl acrylate, isostearyl acrylate, isobutyl methacrylate, 4-hydroxybutyl acrylate, tributyltin acrylate, propane-1,3-diyl diacrylate, trimethylolpropane triacrylate, 4-ethylbenzene acrylate, hydroxyethyl acrylate, hydroxypentabromophenyl methacrylate, pentabromophenyl acrylate, 6-bromo-1-hexyl acrylate, 2-bromoethyl acrylate, 2-chloroethyl methacrylate, 11-phosphonic acid undecyl acrylate, tributyltin acrylate, and 2-(perfluorobutyl)ethyl acrylate.
7. A method for improving poor final sealing of a semi-solid battery as claimed in claim 1 or 3, further characterized in that the initiator comprises: One or more of azobisisobutyronitrile, azobisisoheptanenitrile, azobisdimethylvaleronitrile, cumene hydroperoxide, tert-butyl hydroperoxide, p-menthane hydroperoxide, potassium persulfate, ammonium persulfate, lauroyl peroxide, dibenzoyl peroxide, and dodecanoyl peroxide.
8. A method for improving poor final sealing of a semi-solid battery as claimed in claim 1 or 2, further characterized in that the time for the first infiltration and the second infiltration is 12-48 hours.
9. A method for improving the final sealing failure of a semi-solid battery as claimed in claim 1 or 2, further characterized in that the high temperature curing conditions are: temperature 40-90°C, pressure 300-600kgf, time 2-6h.
Citation Information
Patent Citations
Packaging process of soft package battery and soft package battery
CN117254122A
A scraping device for preparing semi-solid lithium-ion batteries
CN220942044U